Viscosity Decay of Hydrocolloids Under Oral Conditions - Arancibia-Aguilar, C (Elsevier Ltd, 2020)
The aim of this study was to understand the contribution of hydrocolloids to oral structure breakdown of starch-based systems in relation to mouthfeel sensations. For this, carrot purees were prepared using corn starch and a different second thickener (λ-carrageenan, carboxymethylcellulose (CMC), xanthan gum, or an extra amount of starch). The viscosity decay of purees under in vitro oral conditions was measured (starch pasting cell adapted to a rheometer) when shearing at a constant shear rate in the presence of artificial saliva. Sensory properties of purees were described using the Flash Profile technique by a group of 13 panellists. Oral viscosity decay of systems was modelled using a second order structural kinetic equation that included three parameters: initial viscosity, rate of breakdown, and viscosity at equilibrium. Although they had the same initial viscosity, the structural breakdown of the purees in oral conditions varied, depending on the second thickener used. The structure of purees containing xanthan and λ-carrageenan were more resistant under oral conditions exhibiting a slow and smaller breakdown. In contrast, purees containing only starch showed a rapid and large decay because of the complete structure breakdown by amylase. For puree containing CMC, there was also a rapid decrease, but smaller than starch, indicating that part of the structure remained after digestion. Texture sensations freely described by assessors varied according to two main sensory dimensions, that were clearly related to the structural breakdown parameters. As expected, the dimension of thickness (from watery and liquid to thick and viscous) separated base purees from thickened purees and was related to the initial viscosity. The smoothness dimension (from rough and lumpy to the smooth and creamy) was related to the viscosity at equilibrium indicating that after the oral digestion, the characteristics of the remaining structure can explain differences in complex attributes of semisolid systems such as smoothness and creaminess. © 2020 Elsevier Ltd